- 39

- 0

- Problem Statement
- I want to prove that [tex] -\frac{\partial}{\partial p_\mu}\frac{1}{\not{p}}=\frac{1}{\not{p}}\gamma^\mu \frac{1}{\not{p}}[/tex]

- Relevant Equations
- [tex] \not{p}=\gamma^\mu p_\mu[/tex]

This was my attempt at a solution and was wondering where did I go wrong: [tex] -\frac{\partial}{\partial p_\mu}\frac{1}{\not{p}}=-\frac{\partial}{\partial p_\mu}[\gamma^\nu p_\nu]^{-1}=\gamma^\nu\frac{\partial p_\nu}{\partial p_\mu}[\gamma^\sigma p_\sigma]^{-2}=\gamma^\nu\delta^\nu_\mu\frac{1}{\not{p}^2}=\gamma^\mu\frac{1}{\not{p}^2}[/tex]

Any hint would be great! Thank you!

Any hint would be great! Thank you!